2008
DOI: 10.1016/j.neuroscience.2007.10.044
|View full text |Cite
|
Sign up to set email alerts
|

Bone morphogenetic protein-7 reduces toxicity induced by high doses of methamphetamine in rodents

Abstract: Methamphetamine (MA) is a drug of abuse as well as a dopaminergic neurotoxin. We have previously demonstrated that pretreatment with bone morphogenetic protein 7 (BMP7) reduced 6-hydroxydopamine-mediated neurodegeneration in a rodent model of Parkinson's disease. In this study, we examined the neuroprotective effects of BMP7 against MA-mediated toxicity in dopaminergic neurons. Primary dopaminergic neurons, prepared from rat embryonic ventral mesencephalic tissue, were treated with MA. High doses of MA decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
62
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(69 citation statements)
references
References 16 publications
6
62
1
Order By: Relevance
“…7E and F). Similar protective effects with BMP treatment have been noted in models of breast cancer (14) and noninfectious neuronal injury (3,15,39). However, this is the first study to show that BMP signaling acts to reduce apoptosis in neurons following viral infection.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…7E and F). Similar protective effects with BMP treatment have been noted in models of breast cancer (14) and noninfectious neuronal injury (3,15,39). However, this is the first study to show that BMP signaling acts to reduce apoptosis in neurons following viral infection.…”
Section: Discussionsupporting
confidence: 75%
“…In the case of hepatitis C virus, the synergistic activation of BMP signaling and alpha interferon suppresses viral replication (35). In noninfectious models of disease, previous studies have shown that modulating TGF-ā¤ signaling is protective in a murine model of Alzheimer's disease (36), and augmenting BMP signal activation can protect cells and neurons following oxidative stress (15), stroke (40), or other cellular injuries (3,44). However, to our knowledge, the roles of TGF-ā¤ and BMP signaling have not been studied following acute viral infection in the central nervous system (CNS).…”
mentioning
confidence: 99%
“…The differential effects of METH pretreatment on the subsequent exposure might be due to different regimens of drug administration. While chronic low dose pretreatment could induce certain protective genes such as SOD (Superoxide Dismutase) and trophic factors [22], high dose METH binge treatment leads to downregulation of trophic factors [23] and antiapoptotic genes such as bcl-2 [15]. In contrast to the protective effect of low dose chronic preconditioning, our results suggest that intermittent binge exposure causes detrimental instead of protective effects on subsequent METH exposure.…”
Section: Discussioncontrasting
confidence: 57%
“…It has been reported that deficiency in GDNF (Glial cell line-derived neurotrophic factor) level leads to a greater vulnerability to METH binge exposure in GDNF +/2 mice [25]. We have also reported that reduced BMP7 (Bone morphogenetic protein 7) levels in BMP7 +/2 mice caused a larger adverse effect by METH binge treatment [23]. Whether there is a common mechanism for these trophic factors in protecting DA neurons from METH exposure requires further investigation.…”
Section: Discussionmentioning
confidence: 69%
“…BMP-7 induces dopamine neuron differentiation in culture, and promotes survival in the adult nigrostriatal pathway against dopamine toxins in vivo (Lee et al 2003;Harvey et al 2004;Chou et al 2008). Although the direct role of BMP signaling on dopamine neuron induction is unknown, Msx1 and Lmx1a are key determinants of midbrain DNs and are both induced by BMP-Smad activation (TrĆ­bulo et al 2003;Chizhikov and Millen 2004a;Andersson et al 2006).…”
Section: Tgf-b and Neural Developmentmentioning
confidence: 99%